A Decision-Making Framework for Securing Compliant UCO Supply for SAF Production - Widodo, Ahmad Tiko; Novani, Santi (Dinasti International Journal of Economics, Finance & Accounting, 2026)
PT Pertamina Patra Niaga (PPN) faces strategic challenges in sourcing qualified Used Cooking Oil (UCO) to meet Indonesia’s Sustainable Aviation Fuel (SAF) mandates. The government strictly enforces a 1% SAF blend by 2027 and 5% by 2029, pressuring PPN to secure a cost-effective and ISCC CORSIA-compliant supply chain. This study aims to evaluate four strategic alternatives: 100% "Make" UCO, 100% "Buy" UCO, 100% "Make" SAF Domestic, and "Partially Buy" SAF. A quantitative approach using the Analytic Hierarchy Process (AHP) was conducted, collecting primary data through questionnaires from the Board of Directors of PPN's Subholding Downstream. The findings reveal that executives heavily prioritize compliance objectives over short-term commercial gains. The AHP synthesis indicates that the 100% "Make" SAF Domestic strategy is the most optimal (36.2%), strongly supported by a 100% "Buy" UCO upstream model (31.3%). To mitigate supply chain risks and traceability fraud in the informal sector, this study recommends a digitally governed hybrid approach. This involves integrating blockchain traceability and establishing cross-institutional collaborations with the National Nutrition Agency (Badan Gizi Nasional). Ultimately, this framework provides a robust decision tool for establishing compliant and sustainable aviation fuel ecosystems in emerging markets.